Sandalwood Cultivation & Management- Current Understanding, Constraints and Future Perspective - Sharma, Aarju (Indian Journal of Agroforestry, 2025)
Agroforestry tree species, particularly the cultivation of Sandalwood (Santalum album), offers a multifaceted approach to sustainable land utilization, combining economic, environmental, and cultural benefits. This review article synthesizes current literature on Sandalwood cultivation, focusing on host plant selection, management practices, spacing considerations, nutrient transfer mechanisms, heartwood formation, haustoria structure, and associated challenges. Host plant species such as Acacia spp., Casuarina spp., and Eucalyptus spp. play pivotal roles in facilitating sandalwood growth, with specific morpho-physiological characteristics influencing their suitability. Optimal spacing geometries between sandalwood and host species are explored, considering nutrient uptake and water management. Nutrient transfer mechanisms via haustoria reveal complex interactions between sandalwood and host plants, impacting growth and development. Additionally, insights into heartwood formation, genetic material exchange, and constraints such as pests, diseases, and environmental stresses are discussed. The article underscores the need for further research to enhance understanding of sandalwood cultivation, particularly in the context of agroforestry systems and changing climatic conditions. Improved management practices and long-term studies are essential for maximizing the potential of sandalwood cultivation as a sustainable agroforestry endeavor.